Endoplasmic Reticulum Stress-Associated Neuronal Death and Innate Immune Response in Neurological Diseases - Shi, Mingming; Chai, Yan; Zhang, Jianning; Chen, Xin (Frontiers in Immunology, 2022)
Neuronal death and inflammatory response are two common pathological hallmarks of acute central nervous system injury and chronic degenerative disorders, both of which are closely related to cognitive and motor dysfunction associated with various neurological diseases. Neurological diseases are highly heterogeneous; however, they share a common pathogenesis, that is, the aberrant accumulation of misfolded/unfolded proteins within the endoplasmic reticulum (ER). Fortunately, the cell has intrinsic quality control mechanisms to maintain the proteostasis network, such as chaperone-mediated folding and ER-associated degradation. However, when these control mechanisms fail, misfolded/unfolded proteins accumulate in the ER lumen and contribute to ER stress. ER stress has been implicated in nearly all neurological diseases. ER stress initiates the unfolded protein response to restore proteostasis, and if the damage is irreversible, it elicits intracellular cascades of death and inflammation. With the growing appreciation of a functional association between ER stress and neurological diseases and with the improved understanding of the multiple underlying molecular mechanisms, pharmacological and genetic targeting of ER stress are beginning to emerge as therapeutic approaches for neurological diseases.